2021
DOI: 10.3389/fimmu.2021.740260
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Fibrosis Is a Risk Factor for Severe COVID-19

Abstract: Increased left ventricular fibrosis has been reported in patients hospitalized with coronavirus disease 2019 (COVID-19). It is unclear whether this fibrosis is a consequence of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection or a risk factor for severe disease progression. We observed increased fibrosis in the left ventricular myocardium of deceased COVID-19 patients, compared with matched controls. We also detected increased mRNA levels of soluble interleukin-1 receptor-like 1 (sIL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
(58 reference statements)
3
12
0
Order By: Relevance
“…In our study, myocardial trichrome staining showed a significant increase in interstitial and perivascular fibrosis in both aerosol-infected and multi-route infected monkeys. This is in line with current reports [ 23 , 34 , 35 ]. At this time, there are no reports of co-staining fibrotic tissue with SARS-CoV-2 antibodies to demonstrate that fibrosis observed is due to the presence of virus particles at those specific areas in the myocardium.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, myocardial trichrome staining showed a significant increase in interstitial and perivascular fibrosis in both aerosol-infected and multi-route infected monkeys. This is in line with current reports [ 23 , 34 , 35 ]. At this time, there are no reports of co-staining fibrotic tissue with SARS-CoV-2 antibodies to demonstrate that fibrosis observed is due to the presence of virus particles at those specific areas in the myocardium.…”
Section: Discussionsupporting
confidence: 94%
“…Few case reports have demonstrated that SARS-CoV2 can immediately infect the myocardium, triggering viral myocarditis. Nevertheless, in the most cases, myocardial lesions are triggered by the rise in cardiometabolic request linked to systemic infection and continuous oxygen depletion induced by severe pneumonia [ 63 ]. This mechanism has been proposed and supports our results—the over expressions of ACE-2 receptors among the two diseased groups versus the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those of Mustroph et al who hypothesized that higher cardiac fibrosis may predispose to progression of severe COVID-19 due to increased cardiac expression of NRP-1, which permits viral cell entry. In addition, troponin I levels are elevated in severe COVID-19 cases [ 63 ]. Glinka et al and Meng et al concluded that the presence of soluble interleukin-1 receptor-like 1 (sIL1-RL1) in higher levels may provoke expression of NRP-1, the transforming growth factor β1 (TGF-β1) co-receptor [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased left ventricular strain as a fibrosis marker was found to predict moderate and severe COVID-19 progression with accuracy (96). Myocardial fibrogenesis is induced by transforming growth factor β1 (TGF-β1) (97, 98).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigating a potential association between PON1 polymorphisms and COVID-19 pointed at a possible positive correlation between M55 and prevalence and mortality of COVID-19, although these findings remain to be validated in larger-scale studies (95). Increased left ventricular strain as a fibrosis marker was found to predict moderate and severe COVID-19 progression with accuracy (96). Myocardial fibrogenesis is induced by transforming growth factor β1 (TGF-β1) (97,98).…”
Section: Disease Ontologiesmentioning
confidence: 99%